(3YbGFO Cgd GdHjJ hGdQO Ydi GdeWQajIs - (3MSGe GdOjf CHh eMeO YHO Gddg Hf RjO GdYfSj GdeOMLjs
(3ChdgG (B:s
(3GdMeO ddg GdPi fhQ bdhH YHGOg GdehMOjf HeYQaJg CeG HYO CjgG GdENhGf abO HdZJfG QSGdJce Ydi CdSfI ENhGfce hecGJHJce dEjVGM GdMb , hWdH GdJMbjb deG jLH ef CUhd GdOjf hGdJabjgg s
(3BNQgG (B:s
(3NWC gDdGA GdeWQajI CYXe ef NWC GdNhGQL HOQLGJ cHjQI , hbO bOefG eG jcTa Yf YXe MGdge SGFQ GdCFeI GdgGOjf Je s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf hGdahGJM HGdSejcs
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds